A welfare economics analysis of China's industrial layout restructuring - Fuxiang Wu; Cai Yue (China Political Economy (CPE), 2018)
Purpose At present, China's industrial spatial layout faces the predicament of over-agglomeration of Eastern China industries and the near disintegration of industrial structure in the central and western regions. The paper aims to discuss this issue. Design/methodology/approach Based on the perspective of differentiated inter-regional labor mobility, this paper constructed a model framework of quadratic sub-utility quasi-linear preference utility function, and conducted model deduction and numerical simulation on causal factors of this spatial imbalance along the two dimensions of individual and regional welfare. Findings The study finds that in the long run, industrial spatial layout imposes a certain threshold limit on the portfolio proportion of differentiated labor. The dilemma of China's industrial spatial layout is attributable to the deviation of the market's optimal agglomeration from the social optimal agglomeration, and to the disfunction of Eastern China's role as an intermediary between the global and the domestic value chain. Originality/value To resolve this predicament of industrial layout, the unitary welfare compensation based on fiscal transfer payment has to be switched to a more comprehensive approach giving consideration to industrial rebalancing.
Keywords: 330; Differentiated labour; Industrial layout; Industrial rebalancing; Welfare compensation